Work Environment, Mentality, And Organizational Culture As Predictors Of Employee Performance: The Mediating Role Of Work Motivation - Andri Arga Kusumah; Herma Wiharno; Yanneri Elfa Kiswara Rahmantya (International Journal of Management and Business Economics, 2026)
Declining employee performance indicators in public sector organizations call for empirical investigation into the multifaceted determinants of performance. This study examines the extent to which work environment, mentality, and organizational culture predict employee performance directly and indirectly through work motivation as a mediating mechanism at the Civil Service Police Unit (Satpol PP) of Kuningan Regency, West Java, Indonesia. Adopting a quantitative descriptive-verificative design, the study incorporated all 172 active civil servants as respondents through a saturated (census) sampling procedure. Structured questionnaires employing a ten-point interval scale were used for data collection. Analytical procedures encompassed validity and reliability testing, classical assumption diagnostics, three-model path analysis, and Sobel's mediation test processed through SPSS v.25. Findings reveal that work environment (β = 0.434), mentality (β = 0.727), and organizational culture (β = 1.230) each exert a statistically significant positive influence on work motivation (R² = 0.865). All three antecedents, alongside work motivation (β = 0.910), likewise demonstrate significant positive direct effects on employee performance. Sobel test results confirm that work motivation significantly mediates each antecedent–performance relationship (Sobel statistics: 4.391, 5.993, and 12.249, respectively; all p < 0.001). Among the tested paths, organizational culture exercises the most potent indirect effect through motivation (coefficient product = 1.119), indicating that performance enhancement is most powerfully achieved when cultural values are internalized alongside motivational support. These findings contribute a holistic structural model linking environmental, psychological, and cultural antecedents to public-sector performance.